Approches comparative et analytique des pratiques funéraires anciennes à Mbanza Kongo (Province du Zaïre, Angola) - Eloi Cyrille Tollo (Afriques)
This paper focuses on the study of burial practices, including biological anthropology and archaeothanatology, through archaeological excavations of two burial sites in the historical city of Mbanza Kongo, the former capital of the Kongo kingdom. Beyond some aspects related to funerary archaeology, the goal of this paper is to understand the chronology of excavated burials, the spatial distribution of graves and their architecture as well as burials methods. The main objective is also trying to understand how in the burials area, local worship practices alight themselves in a dogmatic and ideological environment influenced by Christianity. The paper aims to compare burials dynamism and practices between ancient’s christian and public cemeteries in Mbanza Kongo as well as those in the Northern provinces of the Kongo Kingdom. This medieval African society at the forefront of cultural blending, has experienced various forms of resilience including in the field of burials.